Business Transformation: Organizational Behavioral Science And Its Impact On Effective Marketing Strategies - Windarsari, Wiwin Riski (International Humanity Advance, Business & Sciences, 2024)
Every company needs organizational behavior, where behavior is needed to build good relationships between individuals and groups, and read behaviors in the organization. The current digital era, where competition between companies is very tight. Every company must pay attention to things that are very important and essential in managing marketing in the company. The use of concepts and strategies in marketing activities has implications for optimization in business management as well as for targeted or effective marketing management. This optimization is then expected to maximize company performance, maximize profits and non-profits, and be able to face existing competition and at the same time be successful in cooperating companies.